Использование цветовой визуализации топологических элементов моделей в учебном процессе - Доброскок, Владимир Ленинмирович; Гаращенко, Ярослав Николаевич; Погарский, Андрей Владимирович (Саратовский государственный технический университет, 2014)
Рассмотрены вопросы использования цветовой визуализации элементов триангуляционных моделей промышленных изделий для обеспечения их наглядного представления на базе цветовых моделей RGB и HSV. Представлена структура и основные возможности разработанной подсистемы цветовой визуализации моделей и подсистемы экспорта DBF-образа в PLY, OBJ и OFF форматы.

"Integrated manufacturing engineering" department of National technical university "Kharkiv polytechnic institute" uses modern information technology in educational process. These technologies also include the colour visualization of computer models, which are used to improve the quality of masters training and increase the analysis capacity in research. In the article discussed the colour visualization of triangular models of industrial products for its pictorial presentation provision on the basis of RGB and HSV colour models. The structure and main features of developed subsystems of the colour visualization and export DBF image to PLY, OBJ and OFF formats.
Using the colour visualization of models topological elements in educational process
Keywords: триангуляционная модель; интегрированные технологии; топология; CAD-системы; STL-файл; призматические цвета